Demographic and Health Consequences of Civil Conflict - Guha-Sapir, Debarati; D’Aoust, Olivia (Washington, DC: World Bank, 2012)
Explains that the well-being of individuals and families in conflict and post-conflict states is a key condition for sustainable peace and long-term development, and matches within countries the differences in scale and intensity of civil conflict with the needs of the affected populations. After a steady post-Cold War decline, the number of ongoing civil conflicts in poor countries increased for the first time to 30 in 2007, according to the Uppsala Conflict Data Programme (UCDP). These conflicts subject the civilian population, including women and children, to arbitrary violence and to systematic and long-term deprivations of food and public health services. The size and profile of this population, its essential demographic data, and its health and nutritional status are needed information to help set priorities for interventions both during and after the conflict. The top priorities include infant health, maternal care, food and nutrition, and basic sanitation. Development programming for post-conflict countries should be based on accurate and timely evidence to justify the priorities selected.